2022
DOI: 10.3390/ani12213041
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Relative Abundance of Ungulates and Other Medium and Large Mammals in Flooded Forests in the Dahomey Gap (Togo)

Abstract: “The Dahomey Gap” is a human-derived mostly savannah region that separates the Guineo-Congolian rainforest block into two major units: the Upper Guinean and the Lower Guinean Forest blocks. Several forest patches are distributed throughout this savannah-dominated habitat. The mammal communities in the Dahomey Gap region have been poorly studied. In this paper we analyse the species richness and abundance of, as well as conservation implications for, medium and large mammals (especially ungulates) inhabiting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…In contrast with our results, a study on rodents from arid savannahs in Senegal revealed that diversity and abundance of species was higher in anthropized than in natural habitats (Konečný et al 2010). In addition, a study on medium and large mammals in the Dahomey Gap highlighted the existence of effects (i) species-area and (ii) of the position of the forest patches themselves (relative to human settlements and rivers) with regard to the species diversity and community metrics of fragmented forests (Segniagbeto et al 2022). Our data cannot evaluate whether effect (i) does apply to rodents too.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our results, a study on rodents from arid savannahs in Senegal revealed that diversity and abundance of species was higher in anthropized than in natural habitats (Konečný et al 2010). In addition, a study on medium and large mammals in the Dahomey Gap highlighted the existence of effects (i) species-area and (ii) of the position of the forest patches themselves (relative to human settlements and rivers) with regard to the species diversity and community metrics of fragmented forests (Segniagbeto et al 2022). Our data cannot evaluate whether effect (i) does apply to rodents too.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore the “core–buffer–corridor” model should be applied only in CC projects aimed at single species or guilds, given that, if extended to other species, it could represent a “too short blanket”: in essence, this spatial design can be functional (i.e., an “umbrella” tool) only for a few other species having comparable ecology and dynamics but be ineffective if used to define strategies for maintaining connectivity for many other organisms with different ecological needs. According to this simplified interpretation, the “core–buffer–corridor” design can emphasise charismatic species (e.g., large mammals) while neglecting many others, although they may play a key role in ecosystem processes (Delso et al, 2021; Segniagbeto et al, 2022).…”
Section: The Ecological Network As Paradigm: Strengths Weaknesses And...mentioning
confidence: 99%
“…In Africa, the effects of HF have recently been studied in different biological groups (e.g., plants: Born et al, 2008; Donaldson et al, 2002; Hauber et al, 2022; invertebrates: Davis, 1994, Donaldson et al, 2002; Hauber et al, 2022; Pryke et al, 2015; fish: Medina et al, 2008; amphibians and reptiles: Agbagwa & Ndukwu, 2014; birds: Ncube & Tarakini, 2022; Peters et al, 2008; Segniagbeto et al, 2017; mammals: Arroyo‐Rodríguez & Mandujano, 2009; Bloomfield et al, 2020; Curry et al, 2021; Ernest et al, 2012; Kifle & Bekele, 2022; Segniagbeto et al, 2022), for ecological relationships (e.g., parasitism: Froeschke et al, 2013; pollination: Donaldson et al, 2002; predation: Maina & Jackson, 2003) and in different ecosystems (e.g., forests: Newmark & McNeally, 2018; savannahs: Dimobe et al, 2017), with feedbacks also on human populations (e.g., Reid et al, 2004) and the use of different methodologies, including field surveys as well as interview‐based campaigns (e.g., Dendi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While studying the mammal communities of coastal forest patches in South-eastern Togo, we were «supervised» by local hunters on where to place our camera traps to increase our chances of sighting the rare West African sitatunga (Tragelaphus spekii, or Tragelaphus gratus according to Groves & Grubb, 2011), a species whose presence in Togo has for long been disputed (Amori et al, 2016). Indeed, after just a few days of camera-trapping, we were able to obtain good photos of this antelope, as well as of many other species (Segniagbeto et al, 2022). In the second case, my research team was mapping the distribution of the Chief Goliath beetle (Goliathus cacicus) in Côte d'Ivoire, a species considered very rare and by some even extinct (Luiselli, 2023).…”
Section: Intervie Ws and Con S Ervati On Eco Lo Gymentioning
confidence: 99%